(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Children are very prone to accidents which more often occur in and around the house. These domestic accidents are one of the five leading causes of death in both industrialized and developing countries. Objectives: The present study was conducted to determine the proportion and pattern of domestic accidents among the under 15 children of rural areas of Bangladesh. Methodology: This cross-sectional type of descriptive study was carried out from October 2015 to May 2016. Parents of 735 children below 15 years of age from Kaliakair Upazilla under the district of Gazipur were interviewed through a pretested semi structured questionnaire. The study place was selected conveniently and the sampling technique was purposive type of nonprobability sampling. Results: The present study revealed that, about one fourth (23.4 %)of the 735children were affected by domestic accidents.Among them injuries from sharp objects and falls from heights were equal (33.1% each) and were the leading causes of domestic accidents. The next leading cause was due to burns (8.7%) and then burns from hot liquids were 7.6%,Injuries from blunt objects were 6.4% and drowning were 4.1%. Kerosene poisoning (0.6%), insect bites (0.6%) and snakebites (0.6%) had the lowest incidence. Majority (53.7%) of the children in this study were male and 46.3% were female and their mean age was 7.05 (±3.842)years. Mean age of the affected children was 7.66 (±3.583) years and age group of 7-9 years were largely (29.1%) affected.Male children were affected more (59.3%) than female children.The children of class IV were affected mostly (48.8%). Most of the children of the study as well as the affected children belonged to nuclear families (61.8% & 65.7% respectively). The mean monthly family income of the respondents was 17260.82 (± 12726.70)taka and that of the affected group was 17125(±13303.60)taka. Children living in semi pucca house affected by domestic accidents more (65.1%) than children living in other housing. Most (56.4%) of the accidents occurred in the surroundings of the house and the rest (43.6%) occurred inside the house. Maximum (32.55%) accidents took place in winter, whereas 30.23% in summer, 23.25% in the rainy season, 6.4% in autumn, 6.4% in late autumn, & 1.17% in spring. All the 7 cases of drowning occurred in rainy season. It was found that only 6.98% of affected children suffered from disabilities. Among the affected children 59.8% took treatment and 7% children took preventive measures. Conclusion: From this study it was concluded that nearly a quarter of the children were affected by domestic accidents and the leading causes of the accidents were injuries from sharp objects and falls from heights. To build up awareness and explore the situation in detail, in depth community based epidemiological study may be carried out by covering whole population. J Shaheed Suhrawardy Med Coll 2020; 12(2): 100-108